2017
DOI: 10.1002/suco.201500202
|View full text |Cite
|
Sign up to set email alerts
|

Physical-mechanical behavior of concretes exposed to high temperatures and different cooling systems

Abstract: Over their lifetime, concrete structures can suffer from different pathologies, one of them is exposure to high temperatures, which diminishes their load‐bearing capacity. This study describes how different concrete types were exposed to high temperatures. To simulate fire extinction, where the temperature of the overheated concrete descends suddenly, different cooling systems were applied: slowly cooling in the open air and fast cooling by spraying different water volumes. Several physical–mechanical characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In the past decades, researchers have focused on the mechanical properties of concrete after exposure to elevated temperatures, such as compressive strength, splitting tensile strength and elastic modulus. Results have indicated that the degree of deterioration depends on the peak temperature, exposure time, cooling system and concrete composition [8,9,14,15]. Omer Arioz et al [1] carried out experimental tests to investigate concrete after exposure to elevated temperatures from 200 °C to 1200 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, researchers have focused on the mechanical properties of concrete after exposure to elevated temperatures, such as compressive strength, splitting tensile strength and elastic modulus. Results have indicated that the degree of deterioration depends on the peak temperature, exposure time, cooling system and concrete composition [8,9,14,15]. Omer Arioz et al [1] carried out experimental tests to investigate concrete after exposure to elevated temperatures from 200 °C to 1200 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The specimens completely decomposed and lost their binding properties after exposure at 1200 °C. Germán Ercolani et al [14] explored the effects of elevated temperatures and different cooling systems on the mechanical properties of concrete. The test results revealed that the water cooling method caused serious decrease of compressive strength, while the increase of water volume used for cooling aggravated this trend.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been proposed to measure the concrete degradation depth caused by fire (Kobayashi and Edahiro 2008;fib 2008). These methods can be roughly categorized into four types: (i) estimating the maximum exposed temperature from the color change on the concrete surface (Joongwon et al 2009;Nabi et al 2004;Sheng et al 2018), (ii) estimating the altered calcium hydroxide [Ca(OH) 2 ] depth using chemical methods such as neutralization depth measurement, scanning electron microscopy, differential thermogravimetric analysis, and X-ray diffraction (Heap et al 2013;Lin et al 1996;Pattamad and Danupon 2018), (iii) measuring the strength and hardness of the concrete via the compressive strength, Vickers hardness, and rebound number measured with a Schmidt hammer (Kubilay 2013;Muhammad and Raja 2013;Pattamad and Danupon 2018;Haddad et al 2013;Cao 2017) and (iv) estimating the degraded depth from crack generation using the ultrasonic propagation velocity and impact echo (Chhauda 1976;Ercolani et al 2017;Kubilay 2013;Heap et al 2013;Iwano et al 2017;Ufuk and Michael 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Capillary pores in cement paste provide spaces for water penetration: this increases transport properties. [10][11][12] Water penetration under thawing conditions leads to ice formation in pores at freezing point temperature. 13,14 This causes increase in volume, which in turn enhance pressure on pore interior walls.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, cement type as an effective factor on cement paste formation considerably influences the damage of concrete and mortar . Capillary pores in cement paste provide spaces for water penetration: this increases transport properties . Water penetration under thawing conditions leads to ice formation in pores at freezing point temperature .…”
Section: Introductionmentioning
confidence: 99%